Blessing in text and picture in Israel and the Levant: a comparative case study on the representation of blessing in Ḫirbet el-Qom and on the Stela of Yeḥawmilk of Byblos, Teil 2 - Leuenberger, Martin (Biblische Notizen, 2009)
The present article elaborates the relevance of the topic of blessing in the Levant of the 1st Millennium BCE on the basis of an exemplary case study on two primary sources: The H«irbet el-Qom-inscription (Qom 3) and the stela of Yehiawmilk of Byblos consist of text and picture. In a methodically reflected procedure, both artefacts are compared in order to depict and interpret in an adequate manner the $ rb-basic constellation, which is based on a significant synergy effect of text and picture.